2020
DOI: 10.1186/s12936-020-03495-z
|View full text |Cite
|
Sign up to set email alerts
|

Reduced human-biting preferences of the African malaria vectors Anopheles arabiensis and Anopheles gambiae in an urban context: controlled, competitive host-preference experiments in Tanzania

Abstract: Background Host preference is a critical determinant of human exposure to vector-borne infections and the impact of vector control interventions. Widespread use of long-lasting insecticide-treated nets (LLINs) and indoor residual spraying (IRS) across sub-Saharan Africa, which protect humans against mosquitoes, may select for altered host preference traits of malaria vectors over the long term. Here, the host preferences of Anopheles arabiensis and Anopheles gambiae sensu stricto (s.s.) were ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The overall feeding patterns observed in this study are consistent with those previously described for the primary and secondary vector species in this study, in regions with similar host availability [ 76 – 78 ]. Blood meal analysis, as a proxy for host preference, is confounded by host availability [ 27 , 36 ]; therefore, we used a direct measure of host preference, the METs, to provide supporting evidence of the seasonal shift in host choice in An. arabiensis [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall feeding patterns observed in this study are consistent with those previously described for the primary and secondary vector species in this study, in regions with similar host availability [ 76 – 78 ]. Blood meal analysis, as a proxy for host preference, is confounded by host availability [ 27 , 36 ]; therefore, we used a direct measure of host preference, the METs, to provide supporting evidence of the seasonal shift in host choice in An. arabiensis [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…funestus s.s. being more anthropophilic than An. arabiensis , which rather are more opportunistic [ 11 , 26 , 27 ]. Due to this difference in host preference, An.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in outcome between both studies could be attributed to higher intensities of pyrethroid resistance in the An gambiae sl population in the Benin study and/or to inherent differences in vector species. The An gambiae sl vector population in Benin is highly anthropophagic, feeding almost entirely on humans indoors [21], while An arabiensis tends to be more zoophilic and is less attracted to humans compared to An gambiae sl [22,23]. Susceptibility bioassays showed that the Benin vector population had a high intensity of resistance to pyrethroids with mosquito mortality remaining below 80% even at doses 10 times the diagnostic dose of permethrin and alphacypermethrin.…”
Section: Discussionmentioning
confidence: 99%
“…The experiment was conducted over 12 nights of sampling from 17 to 28 November 2020. While traps were rotated through stations, volunteers once assigned to a particular station remained fixed throughout the experiment to minimize any variation associated with volunteers and their catching stations [ 9 , 21 ]. Mosquitoes were collected hourly (from 18:00 to 07:00) from each trap on each experimental night with catches from each hour placed in hourly labelled paper cups.…”
Section: Methodsmentioning
confidence: 99%